Soybean oligosaccharide, stachyose, and raffinose in broilers diets: effects on odor compound concentration and microbiota in cecal digesta - Xin Zhu; Jizhe Liu; Haiying Liu; Guiqin Yang (Poultry Science, 2020)
Soybean oligosaccharides have been previously shown to be associated with the production of major odor-causing compounds in broilers, although little is known about the role of stachyose and raffinose, which are key components of soybean oligosaccharide, in broiler cecal microbiota and odor compound production. To this end, soybean oligosaccharide, stachyose, and raffinose were added to the birds' diets to investigate their effects on odor compound production and the microbial community characteristics of the cecum in broilers. A total of 300 one-day-old Arbor Acre broilers with similar initial live weight were randomly allocated into 5 dietary groups with 6 replicates of 10 birds. The diets included soybean meal (positive control), soybean meal-free (negative control), 0.6% soybean oligosaccharide, 0.6% stachyose, or 0.6% raffinose. After a 49-D feeding period, both ceca were aseptically removed postmortem, and the contents were collected and analyzed for skatole, indole, volatile fatty acids, and lactic acid by using high performance liquid chromatography. Bacterial communities were detected by using a high-throughput sequencing platform based on IlluminaMiSeq 2500. Levels of skatole and indole tended to be lower in the dietary supplementation of oligosaccharides. The lowest levels of skatole and indole were observed in the stachyose group (P < 0.05), while the highest levels were found in the negative control group (P < 0.05). Concentrations of acetic acid and propionic acid in the stachyose group were increased (P < 0.05) while those of butyric acid and lactic acid were decreased (P < 0.05) compared with the soybean oligosaccharide and raffinose groups. Firmicutes and Bacteroidetes were prevalent in all groups, the proportion of Bacteroidetes was slightly decreased in the stachyose group, and Verrucomicrobia was abundant in the raffinose group (P > 0.05). Bacterial genera Alistipes and Parabacteroides were comparably abundant in the stachyose group, while Bacteroides, Lactobacillus, and Akkermansia were more abundant in the negative control, stachyose, and raffinose groups, respectively. Collectively, these findings demonstrated that dietary oligosaccharide supplementation significantly reduced odor compound production by modulating the cecal microbial community. Compared with soybean oligosaccharide and raffinose, the addition of stachyose into diets may help improve gut fermentation and minimize odor compound generation in broilers.